Selected Topics on Business Informatics Research: Editorial Introduction to Issue 6 of CSIMQ - Fabrizio Maria Maggi; Raimundas Matulevičius (Complex Systems Informatics and Modeling Quarterly)
Business informatics research bridges management and engineering domains and facilitates communication between scientific and practical applications. The sixth issue of the journal of Complex Systems Informatics and Modeling Quarterly contains four publications that present the extended papers from the workshops of the 14th International Conference on Perspectives in Business Informatics Research (BIR 2015) that was organized in Tartu, Estonia, 26-28 August, 2015. The BIR 2015 workshops captured important and novel topics on information logistics and knowledge supply, security and compliance in business processes, and use of ontologies in information systems. Within this context the fifth publication included in this issue complements the topic of the business informatics research with the investigation of a model-driven approach on the gesture-based interaction in information systems.